Improving descriptive writing skills of students through contextual teaching and learning: Exploring the theme of “Home Sweet Home” - Muhammad Andriana Gaffar; Paulina Novarita; Ilfa Hasanah (Universitas Papua, 2025)
This classroom action research aimed to improve seventh-grade EFL students’ descriptive writing skills through the implementation of Contextual Teaching and Learning (CTL) using the theme “Home Sweet Home.” The study applied a quantitative descriptive approach within a two-cycle CAR framework consisting of planning, action, observation, and reflection stages. A total of 28 students participated in the study. Data were collected through pre-tests, post-tests and observation sheets. Quantitative data were analyzed using descriptive statistics (mean and percentage), while qualitative insights from observations supported the interpretation. The average student score improved from 60.10 in the pre-cycle to 79.89 in cycle I, and 82.42 in cycle II. By the end of cycle II, 89.28% of students achieved the minimum mastery standard (≥70). Improvements were evident in students’ use of vocabulary, grammar (particularly there is/there are and prepositions), punctuation, text organization, and engagement. The results confirm that CTL is effective in fostering contextual understanding and enhancing descriptive writing skills in EFL classrooms.